(3TQM dGejI GdYQHs - (3YHO Gddg Hf GdMSjf Hf YHO Gddg GdYcHQj GdHZOGOj, CHh GdHbGA, eMH GdOjf,J (B616 (3g` s
(3ChdgG (B:s
(3CbjehG Hfi Cei UOhQ eWjce aEfi Edi bhe ShGce GdcdGe ai gPG GdHjJ Ydi KdGKI CTjGA s
(3BNQgG (B:s
(3XQa ReGf hgh LeY CeKd hGddg JYdi CYde gPG BNQ TQM dGejI GdYQH s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B46s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs